Free movement of goods in the European Community under Articles 28 to 30 of the EC treaty - Oliver, Peter (Sweet & Maxwell LondonGB, 2003)
Examines a part of the provisions on the customs union viz Articles 28 to 30. In principle, these provisions prohibit quantitative restrictions and measures of equivalent effect on imports and exports between Member States. Considers the powers of the Community to pass legislation to eliminate technical barriers to trade.